CONSERVATION OF GEODIVERSITY IN FERRUGINOUS GEOSYSTEMS - Ruchkys, Úrsula de Azevedo; Gomes, Mauro; Santos, Darcy José dos; Travassos, Luiz Eduardo Panisset (Mercator, 2024)
This study examines the evolution of areas surrounding the bat caves in the Ferruginous Geosystem of Carajás from 1985 to 2022, emphasising the significance of geodiversity conservation in this unique context. The land use and cover transformations analysis reveals critical insights into spatio-temporal changes and escalating environmental degradation risks. The findings enhance the literature on geodiversity conservation and speleology, providing a solid foundation for future research. Monitoring mined areas and their ecological impacts is essential for refining management strategies for these sensitive ecosystems. Furthermore, recent attempts to amend cave protection legislation, particularly Decree 10.935, pose significant conservation challenges, necessitating a critical evaluation of environmental policies and fostering dialogue among researchers, policymakers, and the mining industry. This study highlights the urgent need for a balanced approach between resource extraction and environmental conservation to mitigate adverse impacts on biodiversity and ecological processes. Integrated and evidence-based environmental management is crucial for addressing the challenges of mining activities and regulatory changes, ensuring the protection of caves and their ecosystems for a sustainable future. Keywords : Geodiversity; Bat Caves; Mining Impacts; Landscape Ecology; Environmental Management; Carajás Geosystem; Legislative Changes.